2021
DOI: 10.1136/bmjopen-2021-051584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on postoperative delirium in patients undergoing brain tumour resections: study protocol of a randomised controlled trial

Abstract: IntroductionPostoperative delirium (POD) is a common complication. The incidence of POD is about 25% in non-cardiac surgery and ranges from 10% to 30% in neurological procedures. A lot of trials show that dexmedetomidine might help to reduce the incidence of delirium in patients undergoing non-cardiac surgery. However, the impact of dexmedetomidine on POD for patients undergoing craniotomy and tumour resections remains unclear.Methods and analysisThe study is a prospective, single-centre, randomised, double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As a highly selective α 2adrenergic receptor agonist, dexmedetomidine has emerged for its diverse potentials and is widely applied in cranial surgery [19]. In patients undergoing cranial surgery, dexmedetomidine demonstrates the ability to mitigate anesthetic drug-related neurotoxicity, reduce intracranial pressure, enhance brain metabolism, minimize brain cell apoptosis and necrosis, inhibit the expression of excitatory neurotransmitters, alleviate postoperative pain, and promote overall postoperative recovery [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…As a highly selective α 2adrenergic receptor agonist, dexmedetomidine has emerged for its diverse potentials and is widely applied in cranial surgery [19]. In patients undergoing cranial surgery, dexmedetomidine demonstrates the ability to mitigate anesthetic drug-related neurotoxicity, reduce intracranial pressure, enhance brain metabolism, minimize brain cell apoptosis and necrosis, inhibit the expression of excitatory neurotransmitters, alleviate postoperative pain, and promote overall postoperative recovery [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment protocol has been previously reported. 6 We conducted a prospective follow-up visit and a secondary analysis to explore the effect of dexmedetomidine on chronic incisional pain. This article adheres to the Consolidated Standards of Reporting Trials (CONSORT) statement.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Previous studies have shown that dexmedetomidine provides effective postoperative early analgesia and reduced postoperative opioid requirements for different types of surgeries. [6][7][8][9] Furthermore, a meta-analysis indicated that dexmedetomidine relieved postoperative acute pain intensity and reduced perioperative analgesic consumption in neurosurgery, but the impact of dexmedetomidine on chronic pain needs further study. 10 It has been reported that postoperative acute pain correlates with an increased risk of chronic pain.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…According to our previous study, the incidence of delirium after frontotemporal tumor resections is about 35% [ 26 ]. A meta-analysis indicated that Dex relatively alleviated the incidence of delirium by approximately 54% [ 27 ].…”
Section: Methodsmentioning
confidence: 99%